FACTORS RELATED TO QUALITY OF LIFE AMONG CHILDREN WITH THALASSEMIA MAJOR: A LITERATURE REVIEW - Lailil Fatkuriyah; Ainul Hidayati (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Thalassemia major is a chronic disease in children that harms children quality of life by interrupting physical function, emotional function, social function, and school function. Objectives: This study aims to identify factors contributed to quality of life among children with thalassemia major. Design: The research design used systematic review based on the PRISMA guideline. Data Sources: The source of the articles used three databases including Pubmed, Science Direct, and NCBI with keywords: “quality of life” AND “children” AND “thalassemia major”. The articles were searched from July to September 2021. Review Methods: The data in this study were obtained by reviewing articles from previous studies using PRISMA checklist and PICOS. To assess the quality of article, JBI Critical Appraisal Tools was also used as a guideline. Results: There were 6 articles reviewed according to the inclusion criteria. All the studies showed that the score of quality of life among children with thalassemia major was lower than that of healthy children. The school function among children with thalassemia major was known to have the lowest score from this review. Factors contributed to quality of life among children with thalassemia major according to this review were chelation therapy, pretransfusion hemoglobin, age during the first transfusion, frequency of transfusion, child’s age, family income, parents’ education, hepatomegaly, body mass index, and serum ferritin levels. Conclusion: This review notifies the necessity of developing strategies in improving the quality of life of children with thalassemia major that involves parents, health services, schools, and the government.